Differentiated Learning to Improve the Character Value of the Pancasila Student Profile in IPS Subjects at UPT SMP Negeri 1 Kasui - Setiawan, Adi; Sinaga, Risma Margaretha; Maydiantoro, Albet (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Social Studies (IPS) has a strategic role in shaping the character and national insight of students. However, social studies learning in junior high school is often considered less interesting and less relevant to students’ daily lives, the argument shows that there are still many social studies teachers who use conventional learning methods such as lectures and assignments, which tend to make students passive and less involved in the learning process. This can lead to low student interest and motivation to learn, which in turn has an impact on the less than optimal achievement of learning objectives and internalization of Pancasila Student Profile values. This study aims to identify the effect of implementing differentiated learning strategies on strengthening the character values of the Pancasila Student Profile at SMP Negeri 1 Kasui. The approach used is mixed methods, involving quantitative and qualitative analysis. Data were collected through observations, interviews, and questionnaires of teachers and students during two learning cycles. The results showed that differentiated strategies are effective in supporting students’ character and academic development simultaneously